Important keywords extraction from documents using semantic analysis - Hasan, H. M. Mahedi; Sanyal, Falguni (2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.